Effects of a community pharmacy-based structured medication review on drug-related problems in all-comers with polypharmacy: a randomized, controlled, double-blind, parallel-group trial - Bischof, Thorsten; Schmidt-Ilsinger, Alexander; Hoppel, Magdalena; Kreuzer, Anton; Briganser, Stefanie; Saiko, Philipp; Ergott-Badawi, Susanne; Podroschko, Raimund; Moser, Stephan; Kossmeier, Michael; Jilma, Bernd; Deibl, Stefan; et al. (Frontiers in Medicine, 2025)
BackgroundMedication reviews may help to reduce the burdens of polypharmacy. A medication review type 2a is a structured evaluation of a patient’s pharmacotherapy based on medication history and patient information in a face-to-face interview.MethodsThis multi-center, randomized, patient- and assessor-blind, parallel-group trial was conducted in 14 community pharmacies in Vienna, Austria. Adult outpatients taking ≥8 drugs were eligible. The intervention was a medication review type 2a. At baseline, pharmacists assessed drug-related problems (DRP), a parameter summarizing problematic aspects of pharmacotherapy, in all participants. Pharmacists randomized patients (1, 1) to the intervention, in which they addressed DRPs, or to the control group, in which DRPs were not addressed. A blind pharmacist reassessed DRPs at the second visit after 3–4 months. The primary endpoint was the difference in the number of DRPs between groups after 3–4 months. Secondary endpoints included changes in therapy adherence, health literacy, and number of active ingredients per patient.ResultsBetween August 2022 and August 2023, 220 patients (intervention n = 110, control n = 110) were randomized; 198 completed the primary analysis (intervention n = 98, control n = 100). A medication review reduced DRPs by ~70% (effect size 0.30, 95% CI: 0.27–0.34) compared to the control group. Therapy adherence- and health literacy-related DRPs decreased significantly by ~60% and ~64%, respectively. Furthermore, a medication review decreased the mean number of active ingredients by ~9% in the intervention group compared to the control group.ConclusionA medication review type 2a effectively reduced the number of DRPs.Trial registrationISRCTN14052916.